The use of reverse abdominoplasty for treatment of chemical burn in the thoracoabdominal region - Guilherme Gurgel do Amaral Teles; Bruno De Oliveira Barbosa; Guilherme Henrique de Castro Teixeira; Raphael Bacco da Rocha; Raphael Usero; André Campoli Frisina; Heloisa Tezzoni Rodrigues (Revista Brasileira de Cirurgia Plástica, 2020)
Chemical burn is a challenge owing to its severity compared to thermal burns. The depth and extent of lesions in different areas of the body lead us to look for different possibilities for the best treatment of the patient. A reverse abdominoplasty surgical technique was proposed; this involves a skin flap that could reduce the exposed area of a chemical burn. The result was satisfactory, reducing the patient's treatment, surgical and hospitalization time, highlighting the proposed technique as an important tool for thoracoabdominal reconstruction.